Development and Validation of a Rapid Benefit–Risk Assessment Index for Pediatric Off‐Label Drug Use - Xuejuan Li; Yingna Xu; Guanglei Jin; Wei Jiang; Zebin Chen; Zhihua Zheng; Xiaoling Wang; Xiaolan Mo; Xinyu Liu; Benjie Zhou; Hong Chang; Shaojie Deng; et al. (Journal of Evidence-Based Medicine, 2026)
ABSTRACT Objective To develop and validate a rapid, evidence‐based benefit–risk assessment index for off‐label drug use in pediatrics, thereby promoting standardized clinical decision‐making. Methods Under the auspices of the Guangdong Pharmaceutical Association, a multidisciplinary expert panel from pediatrics, pharmacy, methodology, and ethics was convened. Systematic literature searches informed a preliminary index framework. Three Delphi rounds refined indicators. Weights were assigned using the analytic hierarchy process. Expert‐based validation involved 20 hematology‐oncology experts assessing 10 cases; intraclass correlation coefficient (ICC) and Spearman's correlations evaluated reliability and validity. Results The index consists of 2 primary dimensions (benefits: 56 points; risks: 44 points), 10 third‐level, and 40 fourth‐level indicators, with five prerequisites (e.g., no alternatives, informed consent). The ICC was 0.77 (good reliability); Spearman's correlations were r s = 0.97 (benefits) and r s = 0.68 (risks) (both p < 0.05), indicating strong alignment with expert consensus. Junior experts showed lower correlations (benefits r s = 0.89; risks r s = 0.56) than seniors (benefits r s = 0.97; risks r s = 0.78), highlighting the system's role in standardizing assessments. Conclusion This quantitative index provides an evidence‐based tool for pediatric off‐label drug decisions, supporting clinicians, policymakers, and standardization efforts.